Critical agency and development: applying Freire and Sen to ICT4D in Zambia and Brazil. Issue 1 (2nd January 2018) - Poveda, Sammia; Roberts, Tony
ABSTRACT: This paper draws upon critical theories and the capability approach. It argues for a conceptualization of development as a process designed to enable people to free themselves from structural disadvantage. Amartya Sen has argued that people's "critical-agency" to question and reject unjust social norms is "pivotal" to human development and important for tackling inequalities of any kind. Freire's critical pedagogy, and critical feminism, go further by providing disadvantaged people with the practical means to do this; to identify the structural root causes of unjust social norms and the critical-agency to challenge and change them. Two empirical case studies of ICT4D are presented, from Zambia and Brazil, which draw upon these critical approaches but use them in different ways. The paper argues that ICT4D must go beyond addressing people's immediate practical needs for access to ICT tools and skills, to also address their strategic interest in identifying and tackling the root causes of disadvantage.